Designing and development of an insecticide applicator for the control of brown plant hopper - Ramachandran V R (Department of Farm Power Machinery and Energy, Kelappaji College of Agricultural Engineering and Technology, 1988)
The brown planthopper Nilaparvata Luqens stal. is a dangerous pest which causes, quick and serious damage to rice in South East Asia. In India a serious damage occurred in Kerala during 1973-1976and the estimated loss in this was 12 cores of rupees.